Increased levels of hexacosanoic acid in the brain of Wistar rats: a behavioral study - Marchetti, Desiree; Coelho, Daniella de M; Coitinho, Adriana S; Guzzo, Edson F M; Padilha, Rafael B; Rosa, Gabriel de L; Vargas, Carmen R (Clinical and Biomedical Research, 2021)
Introduction: X-linked adrenoleukodystrophy (X-ALD) is a peroxisomal metabolic disorder associated with mutations in the ATP-binding cassette sub-family D member1 (ABCD1) gene. Practically all male patients with X-ALD develop adrenocortical insufficiency during childhood and progressive myelopathy and peripheral neuropathy in adulthood. However, some male patients develop a fatal cerebral demyelinating disease named cerebral adrenoleukodystrophy. Although the exact mechanisms underlying brain damage in X-ALD are still poorly elucidated, it is known that hexacosanoic acid (C26:0) accumulation represents a hallmark in the pathogenesis of this disease. In this study, we examined whether an overload of C26:0 injected in Wistar rats was capable of causing behavioral changes in these animals. Methods: Egg lecithin in ethanol was dried under a nitrogen stream and mixed with C26:0 methyl ester. Male Wistar rats at 2–3 weeks of age were obtained from Universidade Federal do Rio Grande do Sul (UFRGS), divided into 8 groups, and submitted to an open field test. We then analyzed line crossings (locomotion and exploration), rearing (orienting and investigatory responses), grooming (anxiety manifestation), and latency to move for each animal. Results: Animals subjected to C26:0 administration presented fewer crossings and rearing episodes and a higher latency to move 45 minutes after C26:0 injection. The present work yields experimental evidence that C26:0, the main accumulated metabolite in X-ALD, can cause behavioral alterations in rats such as the impairment of locomotion and exploratory capabilities, as well as a reduction in orienting and investigatory responses. Conclusion: Although our results are preliminary, they are extremely important for future studies that investigate C26:0 accumulation and locomotor impairment in patients with X-ALD.